A Comparative Clinical Study on effect of Sudhakar Churna and Vasa Guggulu in the Management of Urdhwag Amlapitta. - Waghmode, Mahadev Ganpat; Vilas, Babar Vitthalrao (International Research Journal of Ayurveda & Yoga, 2023)
Today’s life style is completely changed. Most of the people cannot perfect in their food habits. They have bad food habits like irregular intake of food, eating of fried foods, excessive use of chillies & masalas in food etc. The improper living style and faulty diet habits generates the imbalance of the body elements vata, pitta & kapha and thus various disorders may occur. Due to this change life style, many people are suffering from dyspepsia. Study design 20 patient in each group and both group subjected to Urdhwag Amlapitta treatment. In thefirst group doses of Vasa Guggul 500mg BID per day in divided doses for period of 30 days and in the 2nd group doses of Sudhakar Churna 1karsha twice a day(6 gm) BID per day in divided doses for period of 30 days. Result In this chapter various observations of geographical elements like Age, Gender & Religion etc. Are presented in the form of diagrams. The result of both groups were analysed statically, compared and results were interpreted in the term of increase or decrease in the parameter. The statistical analysis revealed that both drugs are effective in Urdhwag Amlapitta.